Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae